2017
DOI: 10.1039/c7sc03308g
|View full text |Cite
|
Sign up to set email alerts
|

A functionalized metal–organic framework decorated with O groups showing excellent performance for lead(ii) removal from aqueous solution

Abstract: A novel MOF decorated with O– groups was elaborately constructed and showed excellent performance for Pb2+ removal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
92
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 198 publications
(95 citation statements)
references
References 74 publications
(71 reference statements)
3
92
0
Order By: Relevance
“…As shown in Figure a, the Pb 4 d and Pb 4 f peaks were observed after Mn‐sdc‐2 was immersed in a 100 μ m aqueous solution of Pb 2+ for 24 h; this indicates the existence of Pb 2+ in Mn‐sdc‐2. Compared with pure Pb(NO 3 ) 2 , the Pb 2+ binding energies of 144.7 (Pb 4 f 5/2 ) and 139.8 eV (Pb 4 f 7/2 ; Figure b), so there were clear shifts of 0.6 eV to lower binding energies of 144.1 and 139.2 eV in Pb‐treated Mn‐sdc‐2; this confirms the strong affinities between Pb 2+ and Mn‐sdc‐2 . These results are consistent with those of previous studies…”
Section: Resultssupporting
confidence: 91%
“…As shown in Figure a, the Pb 4 d and Pb 4 f peaks were observed after Mn‐sdc‐2 was immersed in a 100 μ m aqueous solution of Pb 2+ for 24 h; this indicates the existence of Pb 2+ in Mn‐sdc‐2. Compared with pure Pb(NO 3 ) 2 , the Pb 2+ binding energies of 144.7 (Pb 4 f 5/2 ) and 139.8 eV (Pb 4 f 7/2 ; Figure b), so there were clear shifts of 0.6 eV to lower binding energies of 144.1 and 139.2 eV in Pb‐treated Mn‐sdc‐2; this confirms the strong affinities between Pb 2+ and Mn‐sdc‐2 . These results are consistent with those of previous studies…”
Section: Resultssupporting
confidence: 91%
“…In 2017, 3D porous framework [Zn 3 L 1 (BPE) 1.5 ] (H 2 L 1 =4,4′‐azoxydibenzoic acid, BPE=bis(4‐pyridyl)ethylene) functionalized with O − groups were suggested to removal of Pb II (Figure ) because negative charges of the O − groups create electrostatic interaction with Pb II functioning as a driving force in the removal process . They found that the activated MOF material removed 98.12% Pb II (616.64 mg g −1 ) within 7 min at pH 6 as an optimum one.…”
Section: Adsorption Of One Metal Ionmentioning
confidence: 99%
“… Schematic picture of functionalized [Zn 3 L 1 (BPE) 1.5 ] MOF for Pb II catch. Adapted with permission from Ref . Copyright 2019, Royal Society of Chemistry.…”
Section: Adsorption Of One Metal Ionmentioning
confidence: 99%
“…The authors concluded that the high adsorption capacity (616.64 mg g −1 ) and the rapid kinetics of the structure are due to the proper electrostatic interaction of negative charges of the O − groups with Pb II and acceptance of oxygen electrons pairs by Pb II as a Lewis acid. Also, Pb II as a Lewis acid, has lower hydration energy and a larger ionic radius, and could readily accept electrons from the Lewis base of the O − groups . Stock et al.…”
Section: Strategies For Enhancing the Adsorption Performance Of Mofsmentioning
confidence: 99%
“…Post‐synthetic modification (PSM) reactions have been demonstrated to be an attractive and useful tool for introducing the functional groups into MOFs by means of incorporating the organic linkers or unsaturated metal sites into the metal–organic framework . The method also includes ligand functionalizing, ligand replacement, or functionalization of the unsaturated metal sites.…”
Section: Strategies For Enhancing the Adsorption Performance Of Mofsmentioning
confidence: 99%